2021
DOI: 10.1111/pbi.13671
|View full text |Cite
|
Sign up to set email alerts
|

Towards engineering ectomycorrhization into switchgrass bioenergy crops via a lectin receptor‐like kinase

Abstract: public-accessplan).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 74 publications
(100 reference statements)
1
22
0
Order By: Relevance
“…The success of SIGS for plant disease management is largely determined by RNA uptake efficiency, which varies among different pathogens. Some eukaryotic microbes, including B. cinerea , Rhizoctonia solani , Aspergillus niger , and V. dahliae , could uptake environmental RNA efficiently, whereas RNA uptake is modest in Trichoderma virens , undetectable in Colletotrichum gloeosporioides , and limited in P. infestans ( Qiao et al, 2021 ). The efficiency of SIGS application also depends on RNA stability in the environment.…”
Section: Novel Ev- and Rnai-based Tools For Crop Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success of SIGS for plant disease management is largely determined by RNA uptake efficiency, which varies among different pathogens. Some eukaryotic microbes, including B. cinerea , Rhizoctonia solani , Aspergillus niger , and V. dahliae , could uptake environmental RNA efficiently, whereas RNA uptake is modest in Trichoderma virens , undetectable in Colletotrichum gloeosporioides , and limited in P. infestans ( Qiao et al, 2021 ). The efficiency of SIGS application also depends on RNA stability in the environment.…”
Section: Novel Ev- and Rnai-based Tools For Crop Protectionmentioning
confidence: 99%
“…Such an approach can provide effective and sustainable protection to plants. However, the success of SIGS for plant disease management largely depends on the efficiency of dsRNA uptake, which varies among different pathogens ( Qiao et al, 2021 ). The stability of RNA in the environment also affects the efficiency of SIGS ( Mitter et al, 2017 ).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…This hypothesis could be tested by examining whether over-expression of the AMF-inducible SSP genes can enhance the beneficial interactions between the AMS plants and their symbiotic partner R. irregularis and promote the initiation of symbiosis between R. irregularis and the non-host plant species. Similar approach has been successfully used to investigate the role of a P. trichocarpa G-type lectin receptor-like kinase PtLecRLK1 in the initiation of symbiosis between ectomycorrhizal fungus L. bicolor and two non-host plant species ( A. thaliana and Panicum virgatum ) [ 40 , 41 ]. Also, the powerful clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated system (Cas) [ 42 , 43 ] could be used for generating loss-of-function mutants to validate the function of the plant SSP genes predicted in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A G-type lecRLK is required for interactions between Populus trichocarpa and the ectomycorrhizal fungus Laccaria bicolor (Labbé et al 2019 ). Simultaneously, it was shown that expression of LecRLK1 from Populus trichocarpa in non-host switchgrass roots allows colonization by Laccaria bicolor and improves productivity of this potential bioenergy crop exposed to abiotic stress (Qiao et al 2021 ).…”
Section: Regulation Of Cwi Maintenance In Other Plant Speciesmentioning
confidence: 99%